Perhitungan Daya Listrik Pada Portal Parkir Sepeda Motor Di Area Parkir Universitas Dirgantara Marsekal Suryadarma - Widarto, Husnan; Yohannes Dewanto (JURNAL TEKNOLOGI INDUSTRI, 2025)
The motorcycle parking system at Marshal Suryadarma Aerospace University is still operated manually, resulting in the absence of automatic vehicle data recording and reduced parking security. This study aims to analyze the electrical power requirements of a semi-automatic parking portal system based on RFID and IoT, driven by a single-phase AC motor as the main actuator. An experimental method was employed by measuring current and voltage using a clamp meter under three operational conditions: standby, portal opening, and portal closing. The theoretical power values were calculated using fundamental AC power equations and compared with field measurements to determine the accuracy of the system. The results show that electrical power consumption ranges from 4–36 W (standby), 290–310 W (opening), and 285–300 W (closing), with an accuracy of approximately ±80% compared to theoretical values. These findings indicate that the system is capable of providing sufficiently precise power measurements and is suitable for implementation in semi-automatic parking systems to enhance operational efficiency and reliability.